2018
DOI: 10.1177/0047239518757986
|View full text |Cite
|
Sign up to set email alerts
|

Interaction With Educational Games in Hybrid Virtual Worlds

Abstract: This research links learner engagement with interactions when Hybrid Virtual Learning models are used. Various aspects have been considered, such as learners’ prior experiences related to virtual worlds, their preconceptions regarding their use as a learning tool, and the impact that instructional designers’ choices have on enhancing the opportunities for interactions. In this article, the impact that educational and leisure games have on university students’ engagement is examined. The findings suggest that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…given by the teachers during online classes and quite a number of the respondents also communicate with their peers during online classes. Thus, these findings on promoting meaningful learners' engagement in the virtual platform were in accordance with (Christopoulos et al, 2018;Eric, 2020;Warford, 2014). Lamia et al (2020) rightly identified fewer studies that were based on students' interest in online learning.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…given by the teachers during online classes and quite a number of the respondents also communicate with their peers during online classes. Thus, these findings on promoting meaningful learners' engagement in the virtual platform were in accordance with (Christopoulos et al, 2018;Eric, 2020;Warford, 2014). Lamia et al (2020) rightly identified fewer studies that were based on students' interest in online learning.…”
Section: Discussionsupporting
confidence: 65%
“…Learner engagement is an indispensable requirement for learning and vital to academic achievement in online learning (Gallagher et al, 2016;Omar et al, 2012), and Haron et al (2017) defines it as an active learner in learning activities. In the use of technology instruction in enhancing learners' activities, the virtual platform has to be efficient because the quality and type of online teaching can promote meaningful learners' engagement (Christopoulos et al, 2018;Eric, 2020;Warford, 2014). Dougherty and Andercheck (2014) studied the use of a virtual platform (Facebook) to engage learners in a large introductory course and revealed that the Facebook platform proved effective as a powerful tool for engaging learners.…”
Section: Learner's Participation and Engagement In Technology-enhanced mentioning
confidence: 99%
“…In addition, to attain the second objective of learning in the virtual world, the scenarios were formulated in line with gamification principles that "gamify" various real-world problem situations and learning occasions. Gamification can enhance learning activities with motivational affordances in order to invoke "gameful" experiences and further behavioral outcomes [53,54]. In the 3D world, there have been integrated virtual pedagogical agents that are Non-Player Characters (NPC), and which can accompany students during the study and provide them with various game-based learning activities.…”
Section: The Virtual Reality Educational Environmentmentioning
confidence: 99%
“…As educational programs continue to gain ground in curriculum-aligned contexts globally, there is a persistent need for educators and instructors to offer their support. Student engagement across different educational fields is dependent on the appropriateness of the learning tasks that inform their academic activities and thus shape their future professional practices [64][65][66]. Likewise, given the professional character that such programs have, the development of a better understanding of the self-directed and collaborative efforts that students make is needed.…”
Section: Discussionmentioning
confidence: 99%